2020
DOI: 10.1101/2020.03.30.016097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Entraining movement-related brain oscillations using rhythmic median nerve stimulation

Abstract: Non-invasive brain stimulation techniques delivered to cortical motor areas have been shown previously to: modulate cortical motor excitability; entrain brain oscillations; and influence motor behavior; and have therefore attracted considerable interest as potential therapeutic approaches targeted for the treatment of movement disorders. However, these techniques are most often not suitable for treatment outside of the clinic, or for use with young children. We therefore investigated directly whether rhythmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…The only significant difference in the aftereffect seen here was greater desynchronization in the 8-12Hz band following 20Hz rhythmic stimulation compared to arrhythmic. This contrasts with recent findings which indicated that there was greater mu and beta desynchronization and increased beta rebound following 19Hz arrhythmic stimulation (Maiquez et al, 2020)(preprint). On inspection of the data reported by Maiquez and colleagues, there is a short period of increased mu suppression during and following rhythmic stimulation as seen in our data.…”
Section: Aftereffects Of Rhythmic Stimulationcontrasting
confidence: 90%
See 2 more Smart Citations
“…The only significant difference in the aftereffect seen here was greater desynchronization in the 8-12Hz band following 20Hz rhythmic stimulation compared to arrhythmic. This contrasts with recent findings which indicated that there was greater mu and beta desynchronization and increased beta rebound following 19Hz arrhythmic stimulation (Maiquez et al, 2020)(preprint). On inspection of the data reported by Maiquez and colleagues, there is a short period of increased mu suppression during and following rhythmic stimulation as seen in our data.…”
Section: Aftereffects Of Rhythmic Stimulationcontrasting
confidence: 90%
“…This suggests that the typical mu band desynchronization seen during movement is maintained in the rhythmic condition. However, further findings by the same authors also describe greater beta desynchronization and increased beta rebound following 12Hz arrhythmic stimulation (Morera Maiquez et al, 2020). We hypothesise that these differences in beta aftereffects may have arisen due to a combination of several factors.…”
Section: Aftereffects Of Rhythmic Stimulationmentioning
confidence: 51%
See 1 more Smart Citation
“…Rhythmic stimulation could prove therapeutically beneficial for the diseases related to hyperexcitability within the sensorimotor cortex, such as Tourette syndrome [39], [60] and the rehabilitation about the body function, such as movement [61], speech and language [62]. Previous studies have shown that rhythmic stimulation, for example transcranial magnetic stimulation [63] and electrical stimulation [38], leads to the synchronization of oscillation response, which includes the characteristics of continuous oscillations, phase resetting in SEFs, and the increased ITPS values at stimulation frequency on somatosensory cortex [38], [64]. The measurement results using OPM-MEG in this paper replicate the aforementioned findings.…”
Section: Discussionmentioning
confidence: 99%